LA COLLECTE ET L’ÉVACUATION DES EAUX USÉES À BAMAKO : CAS D’UN DISPOSITIF SEMI-COLLECTIF, LES SYSTÈMES DE MINIÉGOUTS DE BANCONI-FLABOUGOU ET DE SOGONIKO - Hamadoun, Traore (European Scientific Journal, ESJ, 2015)
In Bamako, like in the majority of south of Saharan cities, there is a very fast demographic growth moving from 658 275 inhabitants in 1987 to 1 016 514 in 1998, then 1908104 in 2009 (INSAT, 2010). For a few decades, the town has been suffering from a notorious lack of collective equipments for the collection and cleaning up of domestic waste water. If the issue of access to drinking water is a major problem for the inhabitants of Bamako, the issue of the collection and cleaning-up of waste water remains even more problematical. The problem is more severe in the districts that have long been considered to be precarious then rehabilitated with regard to their location and to the difficult economic conditions of their inhabitants. Initiatives have been taken here and there across the town for a more collective management of waste water with various results. Before the generalisation of these operations in several districts, a test stage has been observed in Bozola with ten or so households. This article is not an evaluation of a management strategy of waste water implemented by certain districts; it rather presents things as experienced at Banconi in commune I and at Sogoniko in Commune VI of the capital city Bamako. Widely known under the name of mini sewers, these devices constitute without any doubt a textbook case to popularize in the outlying districts once the limits are identified and adjusted in their conception and implementation. The quantitative data have been collected from 96 participants and the qualitative data have been collected thanks to several interviews conducted with the communal authorities and some technicians.